Aktivitas Anti Cendawan Ekstrak Daun Sereh Wangi (Cymbopogon nardus L.) Terhadap Colletotrichum sp Penyebab Penyakit Antraknosa Pada Buah Cabai (Capsicum annum L.) Secara In Vitro Dan In Vivo - Mohamad Ana Syabana; Andree Saylendra; Deri Ramdhani (Faculty of Agriculture, Pattimura University, 2015)
The aim of this research was to examine in vitro and in vivo anti fungal activity of citronella leaves extract against Colletotrichum sp caused antrachnose disease on chilli. The in vitro and in vivo research used randomized completely design (RCD) with one factor and five level. The factor was citronella leaves extract and the level were 0,1 % (v/v), 0,2 % (v/v), 0,3 % (v/v), 0,4 % (v/v), 0,5 % (v/v). Negative control treatment was conducted by growing Colletotrichum sp on PDA (in vitro) and chili (in vivo) without citronella leaves extract while positive control was conducted by growing Colletotrichum sp on PDA (in vitro) and chili (in vivo) containing synthetic fungicide. The in vitro study showed that the higher concentration of citronella leaves extract caused higher growth inhibition of Colletotrichum sp. Whereas the in vivo study resulted that higher concentration of citronella leaves extract caused lower incubation period of Colletotrichum sp, intensity of disease and weight loss of chillies. The highest concentration of citronella leaves extract (0,5%) has higher antifungal activity compared to other treatments and negative control while lower than positive control.